(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
This study’s purpose is to reveal and determine the implementation model of the distribution of marital property after divorce from the perspective of Madurese local wisdom. This research uses the empirical juridical method; according to Ronny Hanitijo Soemitro, a law that is empirically a symptom of society, on the other hand, can be studied as a variable (independent variable) which causes consequences on various aspects of social life. In social studies, the law is not conceptualized as an independent (autonomous) normative phenomenon, but as social institutions which are associated in real terms with other social variables. The results of this study are: a model for the implementation of post-divorce marital property distribution in the perspective of Madurese local wisdom, with the wisdom of distributing marital assets after divorce by distributing them into several models or forms as follows: (1) following the distribution model according to the positive legal arrangement of Indonesia, namely what is regulated in state law and is decided by the Religious Court, that the distribution of marital assets, namely widows or divorced widowers, each has the right to a half of the marital assets as long as it is not stipulated otherwise in other agreements in marriage. Meanwhile, based on the Article 37 of Law Number 1 the Year 1974 concerning the marriage, if the marriage breaks up due to divorce, marital assets is regulated according to their respective laws. Meanwhile, according to the Civil Code (KUH Perdita), Article 128, after the dissolution of marital assets, their marital assets are divided between husband and wife, or between their heirs, without question of which party the goods originated from. (2) the post-divorce model of the distribution of marital assets in the perspective of Madurese local wisdom is based on the wisdom of each individual soul or soul of a divorced husband and wife. The wisdom of each of these minds or souls is partly rooted in the Madurese community, which in this paper is called wisdom. As part of local wisdom in Madura, the distribution of marital assets is carried out by means of mediation (abeq remember) attended by community leaders.